Contrast-enhanced ultrasound of granular cell tumor in breast: A case report with review of the literature - Wang, Huanyu; Feng, Duo; Zou, Tianhui; Liu, Yao; Wu, Xiaoqin; Zou, Jiawei; Huang, Rong (Frontiers in Oncology, 2022)
Granular cell tumor is an infrequent, predominantly benign tumor originating from Schwann cells. Granular cell tumor of the breast (GCTB) can simulate breast malignant carcinoma on the clinical assessment. We herein present a rare case of GCTB which recurred in the contralateral breast. We believe the contrast-enhanced ultrasound (CEUS) findings of GCTB have never been described. The high similarity of breast malignant carcinoma makes its differential diagnosis difficult on the clinical and radiological features. In this report, we present the CEUS findings from a rare case of GCTB, explore the possible value of CEUS in differential diagnosis between benign breast lesions and malignant ones, and briefly review the literature.